Analysis of the Science Literacy Competency Profile of High School Students on Sound Wave Material - Indasa, Nita; Jauhariyah, Mukhayyarotin Niswati Rodliyatul (Universitas Islam Negeri Ar-Raniry, 2024)
The learning process in the 21st century requires students to have scientific literacy skills. However, in fact, the scientific literacy skills of Indonesian students are relatively low and tend to decline every year. The purpose of this study was to describe the scientific literacy profile of high school students for the competency aspect in the material of sound waves. This study uses a quantitative approach with a descriptive analysis method. The study was conducted in May 2024 at one of the State High Schools in Nganjuk Regency. The population in this study was 72 students. The research instrument used was a scientific literacy test that had been declared valid with an average Percentage of Agreement (PoA) of 96.43. The data analysis technique used quantitative descriptive analysis from the results of calculating the level of scientific literacy of students. The results of the study obtained a profile of scientific literacy competencies of students of 3% very low, 51% low, 33% sufficient, and 13% high. The percentage for each indicator of scientific literacy competency obtained by students is 43% for the competency of explaining phenomena scientifically, 33% for the competency of evaluating and designing scientific investigations, and 23.6% for the competency of interpreting data and evidence scientifically.